A novel thixotropic magnesium phosphate-based bioink with excellent printability for application in 3D printing. Issue 27 (28th June 2018) - Chen, You; Wang, Yihan; Yang, Qian; Liao, Yuxi; Zhu, Bin; Zhao, Guoru; Shen, Ru; Lu, Xiaobo; Qu, Shuxin
Abstract : A novel magnesium phosphate-based gel (TMP-BG) with excellent printability was developed for application in 3D printing. Abstract : The emergence of 3D bioprinting is expected to solve the present puzzle in the field of regenerative medicine. However, the appropriate bioink was lacking due to the rigorous requirement of high printability and biocompatibility, which was often contradictory. In this study, a novel thixotropic magnesium phosphate-based gel (TMP-BG) was prepared and its application in 3D printing was explored. The stable gel could be synthesized by adjusting the ratio of ternary reactants (NaOH, Mg(OH)2, and H3 PO4 ). Moreover, the structure, morphology, particle size and composition of TMP-BG were characterized. Furthermore, the rheological and thixotropic behaviors and degradation of TMP-BG were investigated. The printability of TMP-BG was tested by using the extrusion-based 3D printer. The biocompatibility of TMP-BG was evaluated in vitro . The composition of TMP-BG was MgNa3 H(PO4 )2, which was of nanometer and sub-micro scale and easily formed a complex three-dimensional porous structure. Rheological results showed that the gel had notable shear thinning behavior and good thixotropy, which could provide the TMP-BG with injectability and formability simultaneously. In addition, the thixotropic mechanisms of TMP-BG were speculated to be a model of "house of cards". Finally, TMP-BG could be printed into large-sized and different complex three-dimensional structures. Results of the MG-63 cell viability and cell proliferation confirmed the biocompatibility of TMG-BG. The present newly developed TMP-BG has the potential to be used as 3D printing bioink involving living cells for future applications in regenerative medicine.